PENYELESAIAN WICARA MELALUI PERADILAN OLEH MAJELIS UTAMA DESA PAKRAMAN (MUDP) PROVINSI BALI - Somya Putra, I Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
This study aim to describe and analyze in debt about the basic authority in resolving Main Assembly of Pakraman Village or Majelis Utama Desa Pakraman (MUDP) Bali Province speech by justice and how to talk through the judicial settlement process by MUDP Bali Province. This research used normative legal research based legal document research and library research. The conclusion in this study, that authority obtained MUDP Bali to finish the speech obtained a mandate by Council Decision No. 050 Main Pakraman / Kep / Psm-1 / MDP Bali / III / 2006 concerning the results of the Great Pasamuhan I MDP Bali and Completion of speech through the courts by MUDP Bali has been arranged by the Decision of the MDP Bali Number: 002 / Skep / MDP Bali / IX / 2011 on the Implementation Guidelines and Technical Guidelines Speech by Assembly Resolution Pakraman (MDP) Bali as a form of autonomy that is owned by Pakraman.
Keywords: Dialogue; Justice; Main Assembly of Pakraman Village (MUDP) Bali Province